The supply of dentists in the Philippines , a situationer - Mabunga, S.T.Y (The Journal of the Philippine Dental Association)
This study is a review of secondary data on the supply of dentists in the Philippines from information gathered from various government and non-governmental agencies. It was done to determine general trends in the supply and stock of dentists as well as have an overview of the oral health human resources in the country. Initial findings indicate an unequal distribution of dentists as well as a large amount of wastage in the production of dentists.